Recent above-ground biomass changes in central Chukotka (Russian Far East) using field sampling and Landsat satellite data - Shevtsova, Iuliia (Dr.); Herzschuh, Ulrike (Prof. Dr.); Heim, Birgit; Schulte, Luise (Dr.); Stünzi, Simone; Pestryakova, Luidmila A.; Zakharov, Evgeniy; Kruse, Stefan (Dr.) (Biogeosciences, 2021)
Upscaling plant biomass distribution and dynamics is essential for estimating carbon stocks and carbon balance. In this respect, the Russian Far East is among the least investigated sub-Arctic regions despite its known vegetation sensitivity to ongoing warming. We representatively harvested above-ground biomass (AGB; separated by dominant taxa) at 40 sampling plots in central Chukotka. We used ordination to relate field-based taxa projective cover and Landsat-derived vegetation indices. A general additive model was used to link the ordination scores to AGB. We then mapped AGB for paired Landsat-derived time slices (i.e. 2000/2001/2002 and 2016/2017), in four study regions covering a wide vegetation gradient from closed-canopy larch forests to barren alpine tundra. We provide AGB estimates and changes in AGB that were previously lacking for central Chukotka at a high spatial resolution and a detailed description of taxonomical contributions. Generally, AGB in the study region ranges from 0 to 16 kg m(-2), with Cajander larch providing the highest contribution. Comparison of changes in AGB within the investigated period shows that the greatest changes (up to 1.25 kg m(-2) yr(-1)) occurred in the northern taiga and in areas where land cover changed to larch closed-canopy forest. As well as the notable changes, increases in AGB also occur within the land-cover classes. Our estimations indicate a general increase in total AGB through-out the investigated tundra-taiga and northern taiga, whereas the tundra showed no evidence of change in AGB.